Re-evaluating paraganglioma surgery – towards optimising patient care. (1st March 2022) - Perry, Helen; Rees, Aled; Scott-Coombes, David; Stechman, Michael
Abstract: Background: Phaeochromocytomas (PCC) and paragangliomas (PGL) are rare neuroendocrine tumours of chromaffin cells that secrete catecholamines. The understanding of their aetiology and management is evolving. This study aimed to examine aspects in the management of PCC and PGL over the last decade. Methods: Patients undergoing surgery for PCC/PGL over an eleven-year period were studied using a prospectively maintained database and electronic hospital clinical portal. Appropriate statistics were then employed. Results: Sixty-nine patients underwent surgery (35 female, median age 52 years (12–82) to treat 57 PCC (inc. 2 bilateral) and 14 PGLs (inc. 2 recurrences). Although PCC and PGL patients were matched for gender and tumour-size, those with PGL were younger (median 40 (12–75) versus 54 (23–82), p = 0.044). PGL patients were also more likely to have a genetic abnormality identified (58.3% versus 16.1%, p = 0.002) and to have a malignant tumour (38.5% vs 6.8%, p = 0.002). Peri-operative blockade regimes were similar, but PGLs more frequently had an open procedure (42.9% vs 5.3% p<0.001). However, when laparoscopic surgery was undertaken, the conversion rate was not significantly different (PGL: 7.1%, PCC 5.2% p = 0.785). Distant and local recurrences were more common in the paraganglioma group (PGL: 25.0%, PCC 1.8%, p=0.002). Conclusions: PGLs represent an even rarer subset of an already rare tumour-type. Access to multi-disciplinary specialists and appropriate decision-making are critical. High incidence of inherited disease, increased malignancy and recurrence rates along with the increased operative complexity favour greater use of open surgery and specialised follow-up to ascertain recurrence, as well as access to high quality genetic counselling services.